Ribosome-Mediated Attenuation of vga(A) Expression Is Shaped by the Antibiotic Resistance Specificity of Vga(A) Protein Variants - Vimberg, Vladimir; Cavanagh, Jorunn Pauline; Novotna, Michaela; Lenart, Jakub; Nguyen Thi Ngoc, Bich; Vesela, Jana; Pain, Maria; Koberska, Marketa; Balikova Novotna, Gabriela (Antimicrobial agents and chemotherapy, 2020)
Vga(A) protein variants confer different levels of resistance to lincosamides, streptogramin A, and pleuromutilins (LSAP) by displacing antibiotics from the ribosome. Here, we show that expression of vga(A) variants from Staphylococcus haemolyticus is regulated by cis-regulatory RNA in response to the LSAP antibiotics by the mechanism of ribosome-mediated attenuation. The specificity of induction depends on Vga(A)-mediated resistance rather than on the sequence of the riboregulator. Fine tuning between Vga(A) activity and its expression in response to the antibiotics may contribute to the selection of more potent Vga(A) variants because newly acquired mutation can be immediately phenotypically manifested.
Keywords: Ribosomes; ribosome-mediated attenuation; ABCF proteins; regulation of gene expression; Staphylococcus haemolyticus; bakteriální proteiny; Macrolides; clindamycin; Bacterial Proteins; makrolidy; Anti-Bacterial Agents; pleuromutilins; Lincosamides; Streptogramin A; linkosamidy; Vga(A); mnohočetná bakteriální léková rezistence; lincosamides; Drug Resistance, Multiple, Bacterial; ribozomy; streptogramin A; antibakteriální látky; antibiotic resistance